Pengaruh Model Pembelajaran Project Based Learning Berbasis Media Laboratorium Virtual PhET terhadap Keterampilan Proses Sains Siswa MAS Insan Kesuma Madani - Zulaika Mannawasalwa; Shinta Marito Siregar; Juliandi Siregar; Rofiqoh Hasan Harahap (Mataram University, 2026)
This study aimed to examine the effect of the Project Based Learning (PjBL) model integrated with PhET virtual laboratory media on students’ science process skills at MAS Insan Kesuma Madani. The research employed a quasi-experimental design with purposive sampling technique. The participants were divided into an experimental class and a control class. Data were collected using a science process skills test instrument. The collected data were analyzed using descriptive and inferential statistics with parametric tests. The findings revealed that the experimental class obtained a higher average N-Gain score (47.5) compared to the control class (20.2). This result indicates a moderate improvement in the experimental group. The hypothesis testing showed a significant difference between the two classes (Sig. 2-tailed = 0.000 < 0.05). These findings confirm that the implementation of the PjBL model integrated with PhET has a positive and significant effect on students’ science process skills. Therefore, this learning model is effective in enhancing students’ science process skills, particularly on the topic of work and energy.